Observational pilot study of patients with carpal tunnel syndrome treated with Nucleo CMP Forte™. (19th November 2018) - Povedano, M; Martínez, Y; Tejado, A; Arroyo, P; Tebe, C; Lorenzo, JL; Montero, J
Aim: Carpal tunnel syndrome (CTS) is a very common entrapment neuropathy characterized by pain and paresthesia in the territory of the median nerve. Although this syndrome has a considerable impact on the patient's quality of life, its medical treatment is far from optimal.Material & methods: We performed an observational study to evaluate Nucleo CMP Forte TM  in patients with electromyography-confirmed, mild–moderate CTS. Pain was assessed using a visual analog scale, electromyogram and the SF-36.Results: Pain decreased significantly after 6 months. Quality of life improved significantly in the pain dimensions. No significant differences were observed in electromyographic findings. No adverse events were reported.Conclusions: Nucleotides could prove useful for the nonsurgical treatment of CTS. Further studies are necessary to confirm this.